Developing An Audiobook To Teaching English To Twelfth Grade First Semester Visual Impairment Students At SLB N 1 Tabanan: Pengembangan Buku Audio Untuk Mengajar Bahasa Inggris Kepada Siswa Tunanetra Kelas XII Semester Pertama di SLB N 1 Tabanan - Cahyadi, Putu Sebastian; Kusuma, I Putu Indra; Pratiwi, Ni Putu Astiti; Ana, I Ketut Trika Adi (DAS Institute, 2026)
This study was conducted to develop audiobooks specifically designed for Visual impairment students 12th grade students to assist in the English learning process. The research sample consisted of Visual impairment students in 12th grade at SLB N 1 Tabanan. This research used a design and development research method that focused on developing English audiobooks for Visual impairment students in 12th grade. The development model used in this research was the Successive Approximation Model/SAM by Allen and Sites (2012). Data collection was conducted through observation, interviews, document analysis, research journals, and expert assessment. The data was then analyzed qualitatively through content analysis and quantitative descriptive analysis. From this analysis, it was found that the audiobook developed met the learning needs of visually impaired students. The audiobook developed was categorized as “very good” in terms of language, design, and content, indicating that the audiobook developed could be appropriate learning material for visually impaired students.